3D printing of microstructured piezoelectric and bioactive PCL-composite scaffolds for bone regeneration - Barkow, Phillip; Polley, Christian; Schöbel, Lisa; Waletzko-Hellwig, Janine; Schnell, Georg; Springer, Armin; Bader, Rainer; Boccaccini, Aldo R.; Seitz, Hermann (International Journal of Bioprinting, 2025)
Despite the self-healing ability of bone tissue, the treatment of critical-size defects and the limited regenerative process in osteoporosis or avascular necrosis demand special medical attention. One of the goals of bone tissue engineering is to develop new patient-specific solutions for bone repair. In this study, we focus on the fabrication of degradable subchondral bone scaffolds made of highly loaded polycaprolactone (PCL) using direct ink writing. Barium titanate (BTO) and the bioactive glass 45S5 (BG) were used as filler materials to modify the material’s piezoelectric, mechanical, and bioresponsive properties. The mechanical properties of our composites are in the range of spongy bone, and a compressive modulus of around 181 MPa was achieved for PCL/BTO and 98.3 MPa for PCL/BTO/BG scaffolds. The use of 40 vol.% BTO in combination with PCL showed piezoelectric properties in the range of bone tissue with a d33 of 0.75 pC/N. While adding BG decreases the piezoelectric properties, it increases the bioactivity and the osteogenic response of primary human osteoblasts. In summary, these novel material compositions provide a promising approach for developing multiphasic scaffolds for bone tissue engineering.
CRIS-Team Scopus Importer:2025-05-16
Keywords: Barium titanate; Bioactive glass; Bone tissue engineering; Composite scaffolds; Direct-ink-writing; Polycaprolactone